Interferon epsilon promotes HIV restriction at multiple steps of viral replication. Issue 5 (3rd January 2017) - Garcia‐Minambres, Albert; Eid, Sahar G; Mangan, Niamh E; Pade, Corinna; Lim, San S; Matthews, Antony Y; de Weerd, Nicole A; Hertzog, Paul J; Mak, Johnson
Abstract : Interferon epsilon (IFNɛ) is a type I IFN that is expressed constitutively in the female reproductive tract (FRT), and contributes to protection in models of sexually transmitted infections. Using multiple cell systems, including reporter cell lines and activated peripheral blood lymphocytes (PBLs), we show that recombinant IFNɛ impairs HIV infection at stage(s) post HIV entry and up to the translation of viral proteins. Consistent with this, IFNɛ upregulated a number of host cell restriction factors that block HIV at these stages of the replication cycle. The potency of IFNɛ induction of these HIV restriction factors was comparable to conventional type I IFNs, namely IFNα and IFNβ. IFNɛ also significantly reduced the infectivity of progeny virion particles likely by inducing expression of HIV restriction factors, such as IFITM3, which act at that stage of infection. Thus, our data demonstrate that human IFNɛ suppresses HIV replication at multiple stages of infection.